Variation of CO2 adsorption in isostructural Cd(II)/Co(II) based MOFs by anion modulation - Singh, Udai P.; Narang, Shikha; Pachfule, Pradip; Banerjee, Rahul (CrystEngComm, 2014)
{A potential multidentate tris-pyridyl ligand has been synthesized, and later employed for the tailoring of four isostructural cadmium(II)/cobalt(II) two dimensional (2D) metal organic frameworks, [[ M(dmpt)(2)(X)(2)].xS](n), where S = solvent